The image of the Orient in the language of private letters of Stanisław Chlebowski (1835–1884) - Olma, Marceli (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The base of proposed reflections made from the perspective of cultural linguistics are private letters by Stanisław Chlebowski — Polish painter who worked at the sultan’s court in Stambul. The aim of the article is a reconstruction of the picture of Orient in lexis and phraseology of the letters. The analysis is conducted from two subiective points of view: the painter’s point of view and point of view of the citizen of the Turkish state. It turns out that Orient and Oriental people are constantly valued by Chlebowski. He uses colloquial Polish, choosing emotional lexemes and morphems. His opinion on Orient is ambivalent, but it is almost convergence with the findings of the researchers of stereotypes about nationality.